2017
DOI: 10.1007/s00429-017-1476-1
|View full text |Cite
|
Sign up to set email alerts
|

Shifted dynamic interactions between subcortical nuclei and inferior frontal gyri during response preparation in persistent developmental stuttering

Abstract: Persistent developmental stuttering is associated with basal ganglia dysfunction or dopamine dysregulation. Here, we studied whole-brain functional connectivity to test how basal ganglia structures coordinate and reorganize sensorimotor brain networks in stuttering. To this end, adults who stutter and fluent speakers (control participants) performed a response anticipation paradigm in the MRI scanner. The preparation of a manual Go/No-Go response reliably produced activity in the basal ganglia and thalamus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 135 publications
(171 reference statements)
4
25
0
6
Order By: Relevance
“…Generally, there seems to be a renewed interest over the past few years in studying anticipation as a critical component of stuttering and the stuttering experience in AWS. [14][15][16][17] There is limited evidence of anticipation in CWS. Early work showed that 45% of 10-to 11year-olds and 38% of 8-to 9-year-olds reported anticipating "sometimes," 18 suggesting that as a group, CWS also anticipate stuttering but less so than AWS.…”
Section: How Often Do People Who Stutter Anticipate Stuttering?mentioning
confidence: 99%
“…Generally, there seems to be a renewed interest over the past few years in studying anticipation as a critical component of stuttering and the stuttering experience in AWS. [14][15][16][17] There is limited evidence of anticipation in CWS. Early work showed that 45% of 10-to 11year-olds and 38% of 8-to 9-year-olds reported anticipating "sometimes," 18 suggesting that as a group, CWS also anticipate stuttering but less so than AWS.…”
Section: How Often Do People Who Stutter Anticipate Stuttering?mentioning
confidence: 99%
“…Approximately 5% of children suffer from stuttering. There is no consensus regarding the pathophysiology of stuttering, but it is thought to be related to a deregulation of the dopaminergic state, with an increase in dopaminergic activity in the brain that can be visualized by positron emission tomography . The involvement of dopaminergic system dysregulation has been confirmed by studies of developmental stuttering in patients with Parkinson's disease and receiving dopaminergic treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding the prevalence of ADHD are highly variable, but a meta‐analysis of 175 studies by Thomas et al reported an overall pooled estimate of 7.2% (95% confidence interval [CI] 6.7–7.8) . Stuttering is a common speech disorder that affects about 5% of children . Data concerning the combination of stuttering and MPH are contradictory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The right inferior frontal cortex is also a key node in the network of brain areas involved in response inhibition (Aron, Robbins, & Poldrack, 2004;Chambers et al, 2007;Xue, Aron, & Poldrack, 2008). It is hypothesized that differences in inhibitory control may account, in part, for brain differences described in developmental stuttering (Alm, 2004;Hartwigsen, Neef, Camilleri, Margulies, & Eickhoff, 2019;Metzger et al, 2018;Neef et al, 2018Neef et al, , 2015Xue et al, 2008). Here, a classic inhibition task was used with PWS whilst recording functional MRI images to test whether there are differences in the neural control of inhibition.…”
Section: Introductionmentioning
confidence: 99%